Cultivating sustainability in language and literature pedagogy : steps to an educational ecology - Bartosch, Roman (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book introduces the notion of 'educational ecology' as a necessary and promising pedagogic principle for the teaching of Anglophone literatures and cultures in a time of climate change. Drawing on scholarship in the environmental humanities and practice-oriented research in education and literature pedagogy, chapters address the challenges of climate change and the demand for sustainability and environmental pedagogy from the specific perspective of literary and cultural studies and education, arguing that these perspectives constitute a crucial element of the transdisciplinary effort of 'cultivating sustainability.' The notion of an 'educational ecology' takes full advantage of the necessarily dialogic and co-constitutive nature of sustainability-related pedagogical philosophy and practice while it retains the subject-specific focus of research and education in the humanities, centring on and excelling in critical thinking, perspective diversity, language and discourse awareness, and the literary and cultural constructions of meaning. This book will be of great interest to academics, researchers and post-graduate students in the fields of language, literature and culture pedagogy, as well as transdisciplinary researchers in the environmental humanities"--
OCLC-licensed vendor bibliographic record.
Keywords: Commonwealth literature (English) -- Study and teaching; English literature -- 21st century -- Study and teaching; Ecology in literature -- Study and teaching; Climatic changes in literature -- Study and teaching; English language -- Study and teaching -- Commonwealth countries; Environmental education -- Study and teaching -- Commonwealth countries; EDUCATION / General